Overview on nanoparticulate formulations for 5-fluorouracil delivery in colorectal cancer treatment - RUSU, Alexandra Doina; PĂTRAȘ, Laura; BANCIU, Manuela (Studia Universitatis Babeș-Bolyai Biologia, 2015)
5-Fluorouracil (5-FU) is an antimetabolite drug used to treat various cancer types, especially colon cancer. Its mechanism of action includes the inhibition of the biosynthetic processes in proliferating cells by inhibiting the normal function of DNA and RNA. 5-FU has a short half-life since 80% of the administered drug is catabolized in the liver. Moreover, the therapies based on the 5-FU administration are accompanied by severe side effects such as immunosuppression, cardiotoxicity, and neurotoxicity. Therefore, the use of the nanoparticle-encapsulated 5-FU can target efficiently colorectal cancer, could reduce the major drawbacks of conventional administration of 5-FU and also increase the drug lifetime and its tumour accumulation, and finally 5-FU therapeutic index will be enhanced. To this end, this article aims to review the recent research regarding nanoparticles encapsulating 5-FU for colorectal cancer targeted therapy.